Training and Accompaniment Innovation Product Superior and Marketing - Supheni, Indrian; Olpah, Hermiliani; Ambarwati, Ambarwati; Nabila, Alfira Juhi; Novianti, Grevita Elma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Collaboration between the Office of Cooperatives and Micro and Small Medium Enterprises (SMEs) with STIE Nganjuk and Griya Batik Sri Rahayu played a very important role in supporting the economic development of Bulu Putren, Putren Village, Nganjuk District Nganjuk Regency. Batik and eco print SMEs are currently the leading products in Bulu Putren, Putren Village, and have prospects very good. The problems main which Become inhibitor developmentof SMEs batik and eco print are in the field of human resources. Because looking for human resources that are tenacious, skilled, and following the field difficult in an era now. Solution solving problem carried out in community service, namely to fulfill the need to increase human resources, is to recruit people who are already skilled from training that has been done, besides that too can conduct independent training for prospective employees if they do not know the world of batik and eco print. Apart from that, what this community service can do is to innovate products and product diversification, provide equipment assistance that supports the production process, for product results will for sale so that more interesting, and practice development sale and promotion which is effective through offline marketing by selling at bazaar stands when there are exhibitions and can also be done online through some media social like Instagram, Facebook, and Marketplaces other. Results after training and assistance show that there are additional variations in the type of product and packaging that can be directly obtained from Upgrade sales turnover.